2022
DOI: 10.1371/journal.pone.0268927
|View full text |Cite
|
Sign up to set email alerts
|

Association of C-peptide and lipoprotein(a) as two predictors with cardiometabolic biomarkers in patients with type 2 diabetes in KERCADR population-based study

Abstract: We sought association between serum Lipoprotein(a) and C-Peptide levels as two predictors with cardiometabolic biomarkers in patients with type 2 diabetes mellitus. This nested case-control study was conducted on 253 participants with type 2 diabetes mellitus and control from the second phase of the KERCADR cohort study. The participants were randomly allocated into case and control groups. The quantitative levels of Lipoprotein(a) and C-Peptide were measured by ELISA. Atherogenic indices of plasma were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Low C-peptide level was associated with increased cardiovascular risk in T2DM [ 31 ], even if glucose variation or severe hypoglycemia was considered [ 32 ]. Nevertheless, the positive association between C-peptide and cardiometabolic biomarkers in patients with T2DM had also been reported [ 33 ]. We observed that the association of C-peptide with cardiovascular risk was different between the participants without previous T2DM and those with previous T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Low C-peptide level was associated with increased cardiovascular risk in T2DM [ 31 ], even if glucose variation or severe hypoglycemia was considered [ 32 ]. Nevertheless, the positive association between C-peptide and cardiometabolic biomarkers in patients with T2DM had also been reported [ 33 ]. We observed that the association of C-peptide with cardiovascular risk was different between the participants without previous T2DM and those with previous T2DM.…”
Section: Discussionmentioning
confidence: 99%